Copper‐Catalyzed Enantioselective Hydroboration of 1, 1‐Disubstituted Alkenes: Method Development, Applications and Mechanistic Studies. Issue 1 (13th November 2017) - Wen, Lu; Cheng, Fengchang; Li, Han; Zhang, Shuoqing; Hong, Xin; Meng, Fanke
Abstract: Cu‐catalyzed enantioselective Cu–B(pin) addition to 1, 1‐disubstituted alkenes generating tertiary alkylcopper complexes that contain a quaternary stereogenic center, followed by the protonation of the complexes are presented. The resulting formal hydroboration products are formed in up to 98 % yield and 99:1 enantiomeric ratio. The C–B(pin) moiety can be converted to a variety of useful functional groups. The method is applied to the enantioselective formal synthesis of ( R )‐ketoprofen. Detailed stereochemical models for enantioselective induction were elucidated through DFT calculations. Abstract : Copper statues : Copper‐catalyzed enantioselective formation of tertiary alkyl‐copper complexes followed by protonation affords hydroboration products in high yields and with excellent enantioselectivity.